Macromolecular organic matter in samples of the asteroid (162173) Ryugu - Yabuta, Hikaru; Cody, George D.; Engrand, Cécile; Kebukawa, Yoko; De Gregorio, Bradley; Bonal, Lydie; Remusat, Laurent; Stroud, Rhonda; Quirico, Eric; Nittler, Larry; Hashiguchi, Minako; Komatsu, Mutsumi; et al. (Science, 2023)
INTRODUCTION Organic compounds in asteroids and comets contain information about the early history of the Solar System. They could also have delivered organic material to early Earth. The Hayabusa2 spacecraft visited the carbonaceous asteroid Ryugu and collected samples of its surface materials, which were brought to Earth in December 2020. RATIONALE We investigated the macromolecular organic matter in the Ryugu samples, measuring its elemental, isotopic, and functional group compositions along with its small-scale structures and morphologies. Analytical methods used included spectro-microscopies, electron microscopy, and isotopic microscopy. We examined intact Ryugu grains and insoluble carbonaceous residues isolated by acid treatment of the Ryugu samples. RESULTS Organic matter is abundant in the Ryugu grains, distributed as submicrometer-sized organic grains and as organic matter dispersed in matrix. The Ryugu organic matter consists of aromatic carbons, aliphatic carbons, ketones, and carboxyls. The functional group compositions are consistent with those of insoluble organic matter (IOM) from primitive carbonaceous CI (Ivuna-type) and CM (Mighei-type) chondritic meteorites. Those meteorites experienced aqueous alteration (reactions with liquid water) on their parent bodies, which implies that the Ryugu organic material was also modified by aqueous alteration on the asteroid parent body. The functional group distributions of the Ryugu organic matter vary on submicrometer scales in ways that relate to the morphologies: nanoparticulate and/or nanoglobular regions are aromatic-rich, whereas organic matter associated with Mg-rich phyllosilicate matrix and carbonates is IOM-like or occurs as diffuse carbon. The observed macromolecular diversity provides further evidence that the organics were modified by aqueous alteration on Ryugu’s parent body. The diffuse carbon is similar to clay-bound organic matter that occurs in CI chondrites and the ungrouped C2-type meteorite Tagish Lake. No graphite-like material was ...